Ingresos y egresos de la Empresa Kineletec S. A. en tiempos de pandemia Covid-19, Babahoyo, periodo 2020-2021. - Moreno Bravo, Anthony Javier (2022)
The control of income and expenses is essential to carry out an appropriate financial management and that the managers of the organization can develop an efficient decision-making process. Similarly, monitoring the company's income and expense records provides up-to-date information for the preparation of financial statements. Reason for which, in the present investigation, the objective was to analyze how the control procedure is carried out with respect to the daily movements that the company Kineletec SA owns, with the intention of defining the main weaknesses that exist in financial management. with respect to the details of income and expenses. The methodology used is made up of a qualitative approach; while the types of research used were field and documentary. The techniques of interview and direct observation were also used, the first is addressed to a representative of the company, while the second consisted of observing the financial statements of the organization. The results of the study reveal that in the company there are no standardized processes for the registration of income and expenses, which conditions the treatment of accounting information, in the same way the absence of management audits of financial procedures was identified, which it prevents to determine the internal weaknesses with respect to the management of the finances.